Modern routines: The Perception of Time and Space in Film Spectator's Memories of Cinemagoing in 1940s Buenos Aires - Gil Mariño, Cecilia Nuria (2021)
The renewal of theoretical and methodological tools, putting the spotlight of film historiography onaudiences and their movie-going routines, has meant a significant shift for the study of national and regional cinemas. The New Cinema History signalled the importance of introducing in-depth, data-based studies of exhibition, distribution and programming, considering individual and collective experiences. One trend in this renewal of cinema history are studies relying on oral testimonies of the elderly to reconstruct their movie-going practices, contributing also to the methodological reflection on the use of memories as historical sources. This article discusses the ways spatial and temporal perceptions appear in oral narratives of movie-going experiences in Buenos Aires during the 1940s and 50s. Based on twenty qualitative interviews with elderly people, we explore how through their imaginaries they build a certain place in the past that contrasts with the perceived present. We trace the ways in which memories are intertwined with the emergence of modern routines and the way the cinematographic experience affected the audience’s cartography of the different environments of Buenos Aires. Film consumption and its imaginaries allowedthe emergence of new sensorial skills related to a changing world.